Microsoft Windows SharePoint services 3.0 step-by-step - Londer, Olga.; English,Bill; Bleeker, Todd; Coventry,Penelope (Redmond, Wash. : Microsoft Press, 2007)
Provides a step by step approach to learning how to use windows sharepoint services to enable effective team collaboration.
Includes index.
osc 30/04/13
Loan
Keywords: Intranets (Computer networks); Web servers